Digitalising Cardiometabolic Risk Surveillance in Higher Education: Development and Validation of an Evidence-Based Web Platform - Laras Putri Gamagitta; Nurul Setyowati (Health Frontiers: Multidisciplinary Journal for Health Professionals, 2026)
Introduction: Non-communicable diseases (NCDs) remain a major global health challenge, while university-based surveillance systems are often fragmented and paper-based, limiting early risk detection and preventive interventions. This study aimed to identify predictors of abnormal blood pressure and develop an evidence-based web surveillance platform for the Integrated Development Post for Non-Communicable Diseases (Posbindu PTM). Methods: A research and development study was conducted, beginning with a cross-sectional needs assessment involving 72 university members recruited through convenience sampling. Demographic, behavioural, anthropometric, blood pressure, and blood glucose data were collected. Multivariable logistic regression identified independent predictors of abnormal blood pressure, informing platform development and expert validation. Results: Abnormal blood pressure was identified in 45.8% of participants. Elevated visceral fat (aOR 5.87), hyperglycaemia (aOR 4.51), physical inactivity (aOR 3.18), inadequate fruit and vegetable intake (aOR 2.64), and age >20 years (aOR 2.31) were significant predictors. The prediction model demonstrated good discrimination (AUC=0.83) and satisfactory calibration. Conclusion: An evidence-informed web-based Posbindu PTM platform provides a scalable digital approach for early cardiometabolic risk surveillance and supports precision public health within university settings.